In vivo testing of a bioresorbable phosphate-based optical fiber - Podrazký, Ondřej; Peterka, Pavel; Kašík, Ivan; Vytykáčová, Soňa; Proboštová, Jana; Mrázek, Jan; Kuneš, Martin; Závalová, Veronika; Radochová, Věra; Lyutakov, Oleksiy; Ceci-Ginistrelli, Edoardo; Pugliese, Diego; et al. (Journal of biophotonics, 2019)
Optical fibers have recently attracted a noticeable interest for biomedical applications because they provide a minimally invasive method for in vivo sensing, imaging techniques, deep-tissue photodynamic therapy or optogenetics. The silica optical fibers are the most commonly used because they offer excellent optical properties, and they are readily available at a reasonable price. The fused silica is a biocompatible material, but it is not bioresorbable so it does not decompose in the body and the fibers must be ex-planted after in vivo use and their fragments can present a considerable risk to the patient when the fiber breaks. In contrast, optical fibers made of phosphate glasses can bring many benefits because such glasses exhibit good transparency in ultraviolet-visible and near-infrared regions, and their solubility in water can be tailored by changing the chemical composition. The bioresorbability and toxicity of phosphate glass-based optical fibers were tested in vivo on male laboratory rats for the first time. The fiber was spliced together with a standard graded-index multi-mode fiber pigtail and an optical probe for in vitro pH measurement was prepared by the immobilization of a fluorescent dye on the fiber tip by a sol-gel method to demonstrate applicability and compatibility of the fiber with common fiber optics.
Keywords: potkani Wistar; oxid křemičitý; fosfáty; Rats; Silicon Dioxide; Animals; krysa rodu Rattus; Rats, Wistar; mužské pohlaví; koncentrace vodíkových iontů; Male; Optical Fibers; zvířata; optická vlákna; Phosphates; Hydrogen-Ion Concentration